Peran Santri Terhadap Kemajuan Filsafat Pendidikan Islam - Idris Sodiq; Hairul Huda; Nida’ Fajri Anjas Ikawati (Universitas Muhammadiyah Jember, 2020)
In the philosophy of Islamic education, students act as one of the determinants of concepts or theories in Islamic education. This is caused by the role of students who jump into the community in order to practice the knowledge that has been obtained from pesantren, or what is often referred to as devotion. So that students also know a lot of things that are lacking in the midst of social life, and students are required to correct the shortcomings of the community. So from this either realize or not realize the students make a very large contribution to the philosophy of Islamic education, where the philosophy of Islamic education is a forerunner or theoretical concept of various Islamic education